2012
DOI: 10.4236/gm.2012.24010
|View full text |Cite
|
Sign up to set email alerts
|

Quick Assessment of Potential Hydrate Promoters for Rapid Formation

Abstract: Hydrate technology has advanced to greater proportions: implementing the high latent heats as refrigerant, safe carbon capture as carbon sequestration in hydrates, purifying rare gases in hydrates, and safe efficient transport of energy using rapid hydrate formation. These account for only a small amount of the fundamental understanding of gas hydrates and the use of such a novel technology. A quick and broad analysis of novel hydrate promoters is needed to assess the potential of other promoter agents. This w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 13 publications
3
5
0
Order By: Relevance
“…Moreover, the signature of the liquid phase is a single band at 887.2 cm –1 . In the CP clathrate sample, the Raman signature is blue-shifted (895.5 cm –1 ) from the liquid as a result of the encapsulation effect within large cages . As noted before, the Raman signatures of solid CP have been found within the clathrate sample because CP is in excess within all samples.…”
Section: Resultssupporting
confidence: 51%
“…Moreover, the signature of the liquid phase is a single band at 887.2 cm –1 . In the CP clathrate sample, the Raman signature is blue-shifted (895.5 cm –1 ) from the liquid as a result of the encapsulation effect within large cages . As noted before, the Raman signatures of solid CP have been found within the clathrate sample because CP is in excess within all samples.…”
Section: Resultssupporting
confidence: 51%
“…This high-frequency shift of the CH 2 stretching bands is due to the encaging of CP molecules in the large cavities (5 12 6 4 ) of sII hydrate, which is in accordance with literature data. 53 The higher intensity of the peaks at 3200 cm -1 relative to the peak at 3400 cm -1 observed in THF and CP hydrate is consistent with the increased ordering of water molecules in the hydrate phase. The observation also agrees with the results reported by Hashimoto et al 54 who reported the Raman spectra of HFC-32 hydrate for which the peak at 3200 cm -1 was larger than that at 3400 cm -1 .…”
Section: Raman Spectra Of Hydratessupporting
confidence: 56%
“…This abnormal point of 18225 s might be mainly attributed to the addition of promoter SDS under a high temperature of 9.5 °C. The specific role of surfactants in promoting hydrate formation is still undetermined 63 . Supposedly, a micelle formation caused by SDS solubility creates several sites for nucleation and enhances the formation rate of hydrates 64 .…”
Section: Discussionmentioning
confidence: 99%